Implementasi Nganggung dan Implikasinya Terhadap Solidaritas Umat di Desa Kace Kecamatan Mendo Barat Kabupaten Bangka - Suparta, Suparta (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2016)
Culture Nganggung held in the village of Kace In particular and in the Pacific Islands in general is a culture that had a positive impact. The positive impact can be seen from the aspect of sociological and theological aspects. Sociological impact can be good communications between citizens and between citizenssilaturrahim media simultaneously. So also from the theological aspect, Nganggung culture can be used as media people to get closer to the creator. Therefore, the procession Nganggung always begins with prayer-prayer ritual led by a cleric, or imam of the mosque that has been trusted by local residents. Thus, culture Nganggung have positive implications on the solidarity of the people.